Modelling of the Annual Mean Urban Heat Island Pattern for Planning of Representative Urban Climate Station Network - János Unger; Stevan Savić; Tamás Gál (Advances in Meteorology)
The spatial distribution of the annual mean urban heat island (UHI) intensity pattern was analysed for the medium-sized city Novi Sad, Serbia, located on the low and flat Great Hungarian Plain. The UHI pattern was determined by an empirical modelling method developed by (Balázs et al. 2009). This method was based on datasets from urban areas of Szeged and Debrecen (Hungary). The urban study area in Novi Sad (60 km2) was established as a grid network of 240 cells (0.5 km ×0.5 km). A Landsat satellite image (from June 2006) was used in order to evaluate normalized difference vegetation index and built-up ratio by cells. The pattern of the obtained UHI intensity values show concentric-like shapes when drawn as isotherms, mostly increase from the suburbs towards the inner urban areas. Results of this thermal pattern and determination of one of the local climate classification systems were used for recommending 10 locations for representative stations of an urban climate network in Novi Sad.